Integrated flood analysis system (IFAS) for Kelantan river basin - Hafiz I.; Sidek L.M.; Basri H.; Fukami K.; Hanapi M.N.; Livia L.; Jaafar A.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Catchments; Disasters; Economics; Flood control; Flood damage; Rain; Rivers; Runoff; Watersheds; Weather forecasting; Analysis system; Catchment area; Financial costs; Flood forecasting; Inundation maps; Natural disasters; Runoff analysis; Socio-economics; Floods